2000
DOI: 10.1021/ma000504h
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Degree of Reversibility of Crystallization and Melting in Poly(ethylene-co-1-octene)

Abstract: The degree of reversibility of crystallization and melting of poly(ethylene-co-1-octene) containing 7.3 mol % (24 mass %) of 1-octene was measured with temperature-modulated differential scanning calorimetry. The sample was crystallized at different cooling rates after excluding self-nuclei of the crystals. The sample was also examined by X-ray scattering techniques, infrared spectroscopy, and standard differential scanning calorimetry. The cooling rates ranged from 0.1 K min -1 to quick quenching. The low-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 78 publications
3
108
0
Order By: Relevance
“…The short sequences without the necessity of chain folding at the edge of lamellae, or in the granular crystallites, fringed micelles, or clusters, may pack quite loosely 4 and contribute to pseudohexagonal crystallinity in ethylene-1-octene copolymers. 60 However, in the case of our heterogeneous copolymers, the attained absolute crystallinity seems sensitive to the comonomer content. In association with the molecular segregation in the melt, this implies that the maximal probability of crystallization of the monomer sequences is only in homogeneous phases.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The short sequences without the necessity of chain folding at the edge of lamellae, or in the granular crystallites, fringed micelles, or clusters, may pack quite loosely 4 and contribute to pseudohexagonal crystallinity in ethylene-1-octene copolymers. 60 However, in the case of our heterogeneous copolymers, the attained absolute crystallinity seems sensitive to the comonomer content. In association with the molecular segregation in the melt, this implies that the maximal probability of crystallization of the monomer sequences is only in homogeneous phases.…”
Section: Discussionmentioning
confidence: 73%
“…The decay of excess heat capacity as a function of time should be attributed to the optimization of crystallographic structure, especially near the fold surface, and without any increase in the lamellar thickness. 35 The excess heat capacity appears fully reversible under temperature modulations and seems not to be associated with the fully melting and recrystallization of granular domains, 60 which should show a hysteresis since their sizes are larger than the critical nucleus during primary nucleation. Actually, this hysteresis has been observed in the low-temperature regions of Figures 2 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…24,26 The physical structure and the properties of inter-and intramolecularly homogeneous poly(ethylene-co-1-octene) are mainly controlled by the constitution of the macromolecule. 27 Because the short-chain branches-MAH existed, the rigidity of the chains was improved, packing of the chains within the crystal was strongly hindered, and the physical parameters like degree of crystallinity and crystallization temperature were strongly influenced. 28 Therefore, the crystal temperature decreases with the MAH concentration.…”
Section: Melting and Crystallization Behaviorsmentioning
confidence: 99%
“…Such self-nucleation from remnant crystalline domains has been qualitatively assigned as the cause of the melt-memory effects. [6][7][8][9][10][11]15,16 However, there have been several investigations where any possible memory from such remnant crystalline domains is deliberately wiped out, but still observing melt-memory effects during second crystallization. 5,[12][13][14][17][18][19][20][21] As a classic example, Schultz observed that the maximum crystallization rate of linear polyethylene can be significantly lower if the sample was prepared at higher melt temperatures.…”
Section: Introductionmentioning
confidence: 99%